Reducing Pending Claims In Indonesia’s National Health Insurance System: Evidence From A Standardized Manual Administration Intervention - Irmawati Mathar; Mertisa Dwi Klevina (Pusat riset dan Inovasi Nasional, 2025)
Pending claims in Indonesia’s National Health Insurance (JKN) system pose a significant challenge, affecting hospital cash flow and administrative efficiency. A high rate of pending claims is often caused by incomplete documentation, misfiled medical records, and delays in verification processes. Optimizing manual administrative procedures may provide a solution to this issue. This study aims to evaluate the effectiveness of a standardized manual administration model in reducing pending claims in a hospital setting. A quasi-experimental pretest-posttest design without a control group was employed. Data were collected from a referral hospital in Indonesia from July to September 2024. A total of 138 inpatient claims were selected using simple random sampling. The intervention involved implementing a standardized manual administration system in August and September. Statistical analysis was conducted using Fisher’s Exact Test with a significance level of p < 0.05. The implementation of the standardized manual administration model significantly reduced pending claims from 70.3% (97/138) in July (pre-intervention) to 36.2% (50/138) in August and further to 11.6% (16/138) in September (post-intervention) (p = 0.000 and p = 0.003, respectively). Additionally, improvements were observed in medical record completeness, supporting examination documentation, and administrative accuracy. A standardized manual administration system effectively decreases pending claims in JKN by improving documentation and claim verification processes. Further research is needed to explore the long-term sustainability of this model and the potential benefits of digitalization.